Public Awareness of Air Pollution and Health Threats: Challenges and Opportunities for Communication Strategies To Improve Environmental Health Literacy. Issue 1 (2nd January 2019) - Ramírez, A Susana; Ramondt, Steven; Van Bogart, Karina; Perez-Zuniga, Raquel
Abstract : Accurate, timely information can be a powerful tool to mitigate harmful effects of air pollution. While national guidelines for environmental risk communication – based on risk and crisis communication principles – exist, little is known how these are operationalized, nor about the effectiveness of existing communication efforts. Moreover, a growing literature on environmental health literacy suggests that communication about environmental risks must move beyond individual behavior education to empower communities to mobilize to reduce environmental threats. This study aimed to identify and critically evaluate public sources of information about the causes and controllability of air pollution and its health effects, and potential disparities in information reach and utility. The case study triangulated data from three sources: Systematic analysis of the public information environment, interviews with regional expert stakeholders, and interviews with community residents. Three themes emerged: 1) Lack of clarity about responsibility for communicating about air quality ( information sources ), 2) Existing air quality communication strategies lack critical information including risk mitigation behaviors and long-term health impacts ( information quality), and 3) Existing air quality communications fail to reach vulnerable populations ( information reach ). This study demonstrates that air quality communication is lacking yet crucially needed. Information about air pollution and health risks focuses on individual risk behaviors but is disseminated using channels that are unlikely to reach the most vulnerable populations. We discuss opportunities to improve the reach and impact of communication of air quality health risks, an increasingly important global priority, situating our argument within a critical environmental health literacy perspective.